DILUCIÓN DE MIEL EN AGUA INDUCE HORMESIS EN LA ACTIVIDAD ANTIBACTERIANA SOBRE Staphylococcus aureus. (FAVE Sección Ciencias Veterinarias, 2021)
In pharmacology, hormesis is defined as the high efficacy of a drug at low doses and a decrease of efficacy at higher doses. In this study, the hormesis phenomenon on the antibacterial activity of honey was assessed. The activity of four honeys (A, D, C and D) were checked by agar plate diffusion method using S. aureus (ATCC 29213) as the test organism. Each honey was tested as follows; on the surface of an agar plate, five stainless steel cylinders with a diameter of 8,14 mm were radially disposed. Onto each cylinder 0,1 mL of the sample honey diluted in water at 50 – 25 - 12,5 -6,25 and 3,125 % v/v were placed. Plates were incubated at 35°C during 24 h. The surface of the cylinder diameter was set as reference antibacterial activity (Ra). The antibacterial activity of each honey was quantitated by the relationship between the surface of the inhibitory zone (Iz) and the surface of the reference activity (Iz/Ra). An increase in the antibacterial activity was observed at a concentration of water greater than 50% in honeys B and C. This hormetic behavior could be considered as indicator of the quality of the antibacterial activity of these honeys.